Evaluation Of Antibiotic Use In Diabetic Ulcer Patients Based On The Defined Daily Dose Method (Ddd) - As Syifa Roidhotul Jannah Putri Widi; Avianti Eka Dewi Aditya Purwaningsih; Novita Sari (Jurnal FARMASIMED (JFM), 2026)
Diabetic ulcers are a complication of diabetes mellitus that manifest as open skin wounds on the feet due to blood vessel disorders and nerve damage. These ulcers are susceptible to infection because bacteria thrive in high glucose environments. Selecting the right antibiotic is crucial in treating these infections. This study aims to predict the pattern of antibiotic prescribing in patients with diabetic ulcer infection in Hospital X Semarang Regency in 2023 using the ATC (Anatomical Therapeutic Chemical) method and DDD (Defined Daily Dose) units. This study is a retrospective descriptive study that analyzes data on diabetic ulcer patients who received antibiotic therapy between January-December 2023. The data collection technique was carried out by purposive sampling, following the inclusion and exclusion criteria. The results of the study of 168 patients with Diabetic Ulcers were found to be more dominant in female patients 53.57% (90 patients) and male patients 46.43% (78 patients). The antibiotic research that was classified as having the highest DDD/100 patient-days value was Ceftriaxone 44.99 DDD, followed by Metronidazole 33.96 DDD and Levofloxacin 26.85 DDD. Meanwhile, antibiotics that were included in the DU 90% segment with the order of highest to lowest values ​​were Ceftriaxone (36.16%), Metronidazole (63.46%), and Levofloxacin (85.04%). The use of antibiotics in diabetic ulcer patients based on the ATC/DDD and DU 90% methods needs to be reviewed periodically because it has the potential to cause the risk of resistance in patients which will then prolong the healing process. Based on the evaluation of antibiotic consumption patterns in diabetic ulcer patients at Hospital X, Semarang Regency in 2023 using the ATC/DDD and DU 90% methods, the antibiotics with the highest DDD/100 patient-days were Ceftriaxone (44.99), followed by Metronidazole (33.96) and Levofloxacin (26.85). These three antibiotics are included in the DU 90% segment, therefore their use needs to be periodically evaluated to ensure the rationality of therapy and to prevent the occurrence of antibiotic resistance.